Clinical Pattern and Frequency of Pediatric Dermatoses at Social Security Teaching Hospital, Lahore - Shumaila Shahzeen, Hafiz Mohammad Wasif, Khalid Mahmood, Mohsin Ali, Sijjad Hussain, Sara Maqsood (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study the clinical pattern and frequency of pediatric dermatoses at Dermatology department Social Security teaching hospital, Multan road Lahore. Methods: Five hundred and thirteen children up to 12 years presenting to the dermatology OPD of Social Security teaching hospital in Lahore located at Multan road with different kind of skin diseases also were included in the respective study consisted on 4 months overall research period. On the basis of age all subjects were segregated into two different groups. One group comprised of patients from 1-6 years and the group from 7-12 years. Diagnosis was made by thorough history and clinical examination mainly. All patients were categorized into various groups on the basis of etiology. Results: Out of 513 children with skin diseases, 323 (62.96%) were males and 190 (37.03%) were females. 300 (62.96%) children were of the age group 1-6 years and 213(37.03%) children were of the age 7-12 years. Different infestations and certain infections were observed in 349 (68.03%) patients and 164 (31.96%) patients presented with various non-infective dermatomes. Conclusion: Infections and infestations were most commonly seen dermatoses as compared to non-infective dermatoses in this study.